Integrated records of environmental change and evolution challenge the Cambrian Explosion - Wood, R; Liu, A; Bowyer, F; Wilby, P; Dunn, F; Kenchington, C; Cuthill, J; Mitchell, E; Penny, A (Springer Nature, 2019)
The ‘Cambrian Explosion’ describes the rapid increase in animal diversity and abundance, as manifest in the fossil record, between ~540 and 520 million years ago (Ma). This event, however, is nested within a far more ancient record of macrofossils extending at least into the late Ediacaran at ~571 Ma. The evolutionary events documented during the Ediacaran–Cambrian interval coincide with geochemical evidence for the modernisation of Earth’s biogeochemical cycles. Holistic integration of fossil and geochemical records leads us to challenge the notion that the Ediacaran and Cambrian worlds were markedly distinct, and places biotic and environmental change within a longer-term narrative. We propose that the evolution of metazoans may have been facilitated by a series of dynamic and global changes in redox conditions and nutrient supply, which, potentially together with biotic feedbacks, enabled turnover events that sustained multiple phases of radiation. We argue that early metazoan diversification should be recast as a series of successive, transitional radiations that extended from the late Ediacaran and continued through the early Palaeozoic. We conclude that while the Cambrian Explosion represents a radiation of crown-group bilaterians, it was simply one phase amongst several metazoan radiations, some older and some younger.